Eating attitudes and energy intakes of female skaters - Ziegler, P.; Hensley, S.; Roepke, J. B.; Whitaker, S. H.; Craig, B. W.; Drewnowski, A. (Medicine & Science in Sports & Exercise, 1998)
This study examined potential links between dietary intakes, body fatness, menstrual status, and hematological and serum iron status in 21 competitive female figure skaters aged 11-16 yr. Results: Body weights and estimated energy intakes were all within normal range for this age group. Higher EAT scores were associated with lower micronutrient, but not lower energy intakes. Menstrual status and iron status were normal. No significant correlations between measures of body fatness, menstrual status, and hematological or serum iron status were observed.